Preparation and Stability of Silicone Dioxide Dispersed in Polyalkylene Glycol based Nanolubricants - M. Z., Sharif; Azmi, W. H.; Redhwan, A. A. M.; Zawawi, N. M. M. (EDP Sciences, 2017)
Nanolubricant is one of the efforts introduced by researchers to increase efficiency in many mechanical application, especially in refrigeration. Two-step method is the most common method used in the process of adding nanoparticles dispersed in base lubricant because of the simplicity of the process to prepare a stable solution. In this work, the SiO2/PAG nanolubricants were prepared using two-steps method without the use of surfactant. The stability of SiO2/PAG nanolubricant was observed trough sedimentation photograph capturing technique and UVVis spectrophotometric test. The results shown that there are minimum sedimentation observed over one month. This result also confirmed via the UV-Vis test; the nanolubricant relative concentration was maintained at over 70 % compared to the initial concentration.